Comparison of Obstetric Outcome among Teenage and Adult Pregnancies in Tertiary Level Hospital - Pathak, Pratima; Shrestha, Sapana; Ghimire, Bijaya; Ghimire, Pratima; Shrestha, Hari Kumar (Journal of Karnali Academy of Health Sciences, 2021)
Background: Teenage pregnancies are a global problem but occur most often in poorer and marginalized communities. It is a high-risk situation for both mother and child because of their vulnerability to many health challenges. This study aimed to compare the obstetric outcome of teenage pregnant mothers (13-19 years) with that of adult pregnant mothers (20–29 years). Methods: Hospital-based cross-sectional comparative study design was adopted. The study was carried out in Nepal medical college and teaching hospital, Kathmandu and Mahakali hospital, Kanchanpur, using a non-probability purposive sampling technique. The data were collected from 94 teenage mothers (13-19 years) and 94 adult mothers (20-29 years) comprising of 2 health facilities. Face to face interview technique was used for the collection of socio-demographic information and obstetric-outcomes related information was collected by observations and hospital/delivery records through pre-designed proforma. Statistical Package for Social Science (SPSS) version 16 was used for data analysis. Descriptive and inferential statistics were used for statistical analysis. Results: The findings of this study showed higher proportion of anemia (28.7% vs. 5.3%, p < 0.001), Pereineal tear (42.3% vs. 16.1%, p = 0.001), pre-term birth (19.1% vs. 5.3%, p = 0.004) and low birth weight infants (30.9% vs. 8.5%, p < 0.001) occurred among teenagers compared to adult mothers (20-29 years). However, caesarean section was found to be lower and vaginal deliveries in higher proportion among teenagers. Conclusions: Teenage pregnant mothers had significantly higher rates of anemia, perineal tear, pre-term birth, and low birth weight. Focusing on girl-child education, strict law to prohibit teenage marriage, proper antenatal care in case if teenage pregnancy occurs can reduce teenage pregnancy and its related complications.